2016
DOI: 10.1007/s11060-016-2170-5
|View full text |Cite
|
Sign up to set email alerts
|

Does where you live influence how your vestibular schwannoma is managed? Examining geographical differences in vestibular schwannoma treatment across the United States

Abstract: The management of small- to medium-sized vestibular schwannoma (VS) remains controversial. Despite a lack of compelling evidence supporting one treatment modality over others, many providers and institutions remain highly biased toward one particular therapy-microsurgery, radiation, or primary observation. The objective of the current study was to estimate the impact of geography on disease presentation and initial treatment of VS in the United States. An analysis of the Surveillance, Epidemiology, and End Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…The importance of the radiation oncologist is similarly reflected in this article. Most previous work has focused on assessing the impact of surgeons on treatment patterns such as mastectomy for breast cancer (38)(39)(40)(41) or active surveillance in prostate cancer (37,42), or primary treatment of vestibular schwannoma (43). Therefore, both this article and the previous report by Jagsi et al (15) represent a novel approach in understanding treatment decisionsdby assessing the impact of the radiation oncologistdand they suggest an increasing need for research, especially because the relative increase in nationwide health care expenditures in radiation oncology far outpaces that in other medical specialties (44).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the radiation oncologist is similarly reflected in this article. Most previous work has focused on assessing the impact of surgeons on treatment patterns such as mastectomy for breast cancer (38)(39)(40)(41) or active surveillance in prostate cancer (37,42), or primary treatment of vestibular schwannoma (43). Therefore, both this article and the previous report by Jagsi et al (15) represent a novel approach in understanding treatment decisionsdby assessing the impact of the radiation oncologistdand they suggest an increasing need for research, especially because the relative increase in nationwide health care expenditures in radiation oncology far outpaces that in other medical specialties (44).…”
Section: Discussionmentioning
confidence: 99%
“…The study described place of residence as a stronger predictor for choice of management strategy than a patient’s age or VS size [12]. Next to referral patterns and availability of care, the authors contribute this to provider or institutional preference [12]. Naturally, in the current study, the proportion of patients assigned to each management strategy can be partially attributed to differences in local availability of care and referral patterns.…”
Section: Discussionmentioning
confidence: 94%
“…The study described place of residence as a stronger predictor for choice of management strategy than a patient’s age or VS size [12]. Next to referral patterns and availability of care, the authors contribute this to provider or institutional preference [12].…”
Section: Discussionmentioning
confidence: 99%
“…Stepanidis et al (2014) demonstrated a decrease in diagnosis of VS in remote areas of Denmark due to lower rates of reporting [48]. Better links between primary and tertiary care might well result in higher diagnostic rates of VS. Carlson et al (2016) found that geographic location impacts both VS presentation and treatment because of variability in regional referral patterns, “provider or institutional treatment preferences, and regional availability of subspecialty expertise” [21]. On the other hand, one could argue that such variabilities should not be very common within the standardized context of NHS; therefore the increased period prevalence observed in some predominantly rural areas of Scotland could well be real.…”
Section: Discussionmentioning
confidence: 99%
“…Only one recent study in the United States has examined the association between geographic variables and differences the treatment strategy of VS using a cohort of 9761 VS cases over an eight-year period [21]. That study, however, utilized spatially disjunct regions for analysis and did not examine the spatial distribution or pattern of VS across the US.…”
Section: Introductionmentioning
confidence: 99%